ANALISA PROPERTIES MATERIAL PIPA ECONOMIZER PLTU JATENG 2 ADIPALA 1 X 660 MW - Martin Fatah; Dhami Johar Damiri; Halim Rusjdi; rafsanjani rafsanjani (Sekolah Tinggi Teknik - PLN, 2018)
A leaking of welding joint in the economizer tube was observed at PLTU Adipala. The tube was just operated for 2 months (1440 hours) since the commissioning. The leaking might be caused by the aggressive working environment of the tube. This aggressive environment might also decrease the performance of material properties. The objective of the research is to investigate the tube material properties after 2 months operation. The material properties was analysed using mechanical, visual and metallography test, i.e. tensile test, hardness test, optical microscope as well as SEM/EDX. It is observed that the yield tregth and UTS of the tube are within SA210 C carbon steel standard. Hardness of the tube is slightly lower than SA210 C standard.. Visual inspection both on fireside and waterside shows corrosion attack. SEM shows pitting corrosion on the inner surface. However, EDX doesn’t show any corrosive species in the inner surface of the tube.